The Willouran basic province of South Australia: Its relation to the Guibei large igneous province in South China and the breakup of Rodinia - Wang, Xuan-ce; Li, X.; Li, Zheng-Xiang; Liu, Y.; Yang, Y. (Elsevier Science BV, 2010)
The Willouran Basic Province in South-Central Australia and the Guibei large igneous province (LIP) in the South China Block are two of the most prominent Neoproterozoic LIPs related to the breakup of the supercontinent Rodinia. The Willouran Basic Province is dominated by tholeiitic mafic dykes (the Gairdner dykes), flood basalts (the Wooltana basalts), and mafic intrusions. The basaltic suites across a distance of more than 1000 km have similar immobile major element compositions, uniform tholeiitic OIB-type trace element distribution patterns, and identical Hf-Nd isotopic signatures. Geochemical analyses from this study imply that their generation may have involved both depleted and enriched mantle sources, similar to that of the Guibei LIP. The age distributions of the two LIPs are also comparable, peaking at ca. 825 Ma. This simultaneous flare-up of mafic magmatism in the two continents, including high-temperature lavas found in the South China Block, coincides with the starting up of widespread continental rifting in Rodinia. We thus speculate that the two LIPs could have been parts of a once contiguous LIP, which was dismembered during the breakup of Rodinia. This work thus provides additional support for the proposed South China-Australia connection in Rodinia.